Determinants of Severe Preeclampsia in Mothers Giving Birth at dr. Dradjat Prawiranegara Hospital in Serang Regency Indonesia - Rina Kartikasari; Weni Marlina; Feling Polwandari; Ayu Kurnia Anggraeni (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Preeclampsia is a condition where a pregnant woman's blood pressure increases accompanied by the presence of protein in the urine. Conditions like this are triggered by the fetus' placenta not functioning or developing properly. Preeclampsia/eclampsia is the second cause after bleeding as a direct cause of maternal death. The aim of the research was to analyze the determinants of the incidence of severe preeclampsia in mothers giving birth at RSUD dr. Dradjat Prawiranegara Serang 2023. This research is an analytical correlative research with a retrospective design. The samples taken used purposive sampling technique, namely 69 mothers who experienced preeclampsia. The results of this study showed that there were mothers giving birth with an incidence of PEB of 69%, there was a relationship between BMI and PEB (p-value 0.000 and OR 5.060 ), there is a relationship between a history of preeclampsia and PEB (p-value 0.000 and OR 9.608), there is a relationship between weight gain during pregnancy and PEB (p-value 0.036 and OR 4,083), there is a relationship between a history of DM and PEB (p-value 0.033 and OR 2,797), and there is a relationship between a history of consuming high doses of calcium and PEB (p-value 0.000 and OR 6.632). The most influential determinant of the incidence of PEB is a history of preeclampsia (p-value 0.005 and OR 7.351).The conclusion of this study is that there is a relationship between BMI, history of preeclampsia, body weight during pregnancy, history of DM and history of consuming high doses of calcium with the incidence of severe preeclampsia, It is hoped that Dr. Drajat Prawiranegara to be able to maintain service quality, especially in providing comprehensive midwifery care.